The Effect of Duration of Use and Hygienity on Microbial Profile of Used Mask Surface Used by Children School in Jakarta - Mahrunnisa, Fitria; Suwarsono, Erike Anggraini; Awaliyah, Vina Izzatul (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is a respiratory infectious disease caused by the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) virus. The main medium of transmission of COVID-19 is droplets from the respiratory tract. One way to prevent this is to wear a mask. In the context of good and correct mask use, the duration of mask use is one of the concerns, because a study shows that microbes in the form of potentially harmful bacteria and fungi can be found in the use of masks for a long duration. In addition, dental hygiene is also a factor in the development of microorganisms after wearing a mask. Children aged 0-18 years are vulnerable to contracting Covid-19, especially from family. However, until now there have been no studies conducted to identify the hygiene of masks used by children. The aims of this study is to determine the hygiene profile of masks used by school children by identifying the type, number of microbes and knowing the factors that affect the hygiene of the use of masks by elementary, junior high and high school age children.Methods: This study is a cross-sectional study by conducting interviews and collecting masks that have been worn by elementary school students in Jakarta. The surface of the face side mask was then swabbed and cultured on Nutrient Agar media. Data were analyzed using the Mann Whitney test.Results: The subjects in this study were 62 children with an age range of 7-13 years with the majority being female as many as 34 children (54.84%). This study found that there was no significant difference between the number of colonies based on tooth brushing activities before using a mask and the duration of mask use (p 0.396; p 0.268), while there was a significant difference with dental caries (p 0.041). In addition, there was a significant relationship between the presence of pathogens in the mask and the activity of brushing teeth before using the mask (p 0.027) with an OR value of 3.709 (95% CI 1.288- 10.685), meaning that respondents who did not brush their teeth before using the mask had a 3.709 times chance of having pathogens in the mask they used. Meanwhile, in terms of the presence of pathogens, there was no significant relationship between the presence of pathogens in the mask with dental caries and duration of mask use (p 0.166; p 0.516). The types of bacteria identified were dominated by non-pathogenic bacteria in humans, such as Staphylococcus epidermidis and Staphylococcus aureus. This could have occurred because it was affected by the pH of the skin surface which tends to be acidic, due to the free fatty acids contained in the skin.Conclusion: Dental and oral hygiene using masks is related to the presence of pathogenic microbes in the use of masks to prevent Covid-19 in children.